Small bowel obstruction secondary to primary enterolith: A rare and delayed complication of radiation enteritis - Charalampos Seretis; Lucy Archer; Mohammed Ali Elhassan; Deborah Gurung; Amitabh Palit; Kassim Zayyan (Clinical Case Reports, 2021)
Abstract Primary enteroliths as a result of pelvic radiotherapy are a rare cause of intestinal obstruction.